A Model-Based Approach for the Qualification of Standard Operating Procedures - Bashatah, Jomana A.; Sherry, Lance (Integrated Communications, Navigation, and Surveillance Conference, 2021)
Standard Operating Procedures (SOPs) define the sequential actions performed by operators to complete a mission. The SOPS are designed to ensure safety and operational efficiency and are especially important for complex, non-normal, and emergency operations. In the aviation industry, airlines derive their SOPs from manufacturer's SOPs to match their company policies and operational constraints. SOPs are designed and revised by Subject Matter Experts (SMEs) and depending on available resources may be tested with a small sample of pilots. Due to the small sample size of subjects and the complexity of the environment and operations, the modified SOPs cannot be exhaustively tested. This is especially true for procedures that must be completed within an Allowable Operational Time Window (AOTW) that varies based on vehicle performance and environmental conditions. In these cases, the Time on Procedure (ToP), also variable due to variance in human performance, must be completed within the AOTW. Verifying the SOP for all the possible combinations of AOTW and ToP is critical to safe operations.This paper describes a formal method to quantify the performance of SOPs while taking into account variability in AOTW and ToP. The SOPs can be modeled and simulated in a Model-based System Engineering (MBSE) tool using standard modeling languages such as SysML and LML. A case study of the method is presented, and the results and limitations are discussed.